"I will take ARVs once my body deteriorates": an analysis of Swazi men's perceptions and acceptability of Test and Start. Issue 4 (2nd October 2017) - Adams, Alfred K; Zamberia, Agostino M
Abstract : Swaziland has the highest HIV prevalence in the world. To mitigate the spread and devastation caused by HIV and to improve the wellbeing of people living with HIV, the country has adopted the latest available HIV prevention campaigns, including "Test and Start". Because evidence from randomised controlled trials has demonstrated a significant risk reduction in HIV transmission when HIV-positive people start antiretroviral therapy (ART) early, Swaziland aims to find these people and link them to treatment. This study presents findings regarding the perceptions of this promising HIV-prevention intervention among men aged 17–69 years. A combination of qualitative methods including focus group discussions (12), in-depth interviews (17), informal conversations and participant observation (21) were used to collect data in two peri-urban communities in 2013–2014. Findings illustrate that men still fear taking an HIV test because of a relatively high probability of a positive test which some still interpret as a death sentence. Other potential barriers to the effectiveness of Test and Start programmes include lack of hospitality in hospitals, fear of starting treatment early related to side effects of ART, poverty, and lack of trust in the financial stability of the Swazi government. We argue that several social factors need to be considered for the Test and Start programme to be more effective.